Analysis of killer cell immunoglobulin-like receptors and their human leukocyte antigen-ligands gene polymorphisms in Iranian patients with systemic lupus erythematosus. (October 2016) - Akhtari, M; Farazmand, A; Mahmoudi, M; Akbarian, M; Ahmadzadeh, N; Mirkazemi, Z; Mostafaei, S; Jamshidi, A R
Objective: Systemic lupus erythematosus (SLE) is an inflammatory autoimmune disease. Natural killer (NK) cells play a critical role in the pathogenesis of autoimmune disorders that mainly express killer cell immunoglobulin-like receptors (KIRs). The present study was undertaken to determine the association of the KIR alleles, genotypes, and KIR– human leukocyte antigen ( HLA ) ligand gene combinations with the susceptibility to SLE. Methods: The genotyping of 17 KIR and 5 HLA loci was performed using the polymerase chain reaction-sequence specific primer (PCR-SSP) method. The study population consisted of 230 SLE patients and 273 ethnical-, age-, and sex-matched healthy controls. The association of the polymorphisms with the prevalence of 11 clinical criteria in patients was analyzed. Results: The carrier frequency of HLA-A-Bw4 was modestly decreased in the SLE patients. The prevalence of hematological and renal disorders was significantly increased in patients with combination of KIR3DL1 + ; HLA-B-Bw4 Thr80+ and KIR2DS1 + ; HLA-C2 + genes, respectively. Female patients with combination of KIR2DL2 + ; HLA-C1 − genes were more likely to develop serositis. In addition the prevalence of renal disorders, oral ulcer and serositis was significantly increased in male patients with KIR3DP1 +, KIR2DS1 +, and KIR2DS3 + genotypes respectively. Conclusion: Our results showed that the presence of activating KIR receptors alone or in combination with their HLA ligands and the absence of inhibitory KIRs in combination with their HLA ligands may activate NK cells and are significantly correlated with the prevalence of renal disease, hematologic disorders, serositis, and oral ulcer in SLE patients.